Insulin-like growth factor I modulates sleep through hypothalamic orexin neurons - Zegarra-Valdivia, Jonathan A. (2020)
Although sleep disturbances are common co-morbidities of metabolic diseases, the underlying processes linking both are not yet fully defined. Changes in the duration of sleep are paralleled by changes in the levels of insulin-like growth factor-I (IGF-I), an anabolic hormone that shows a circadian pattern in the circulation and activity-dependent entrance in the brain. However, the specific role, if any, of IGF-I in this universal homeostatic process remains poorly understood. We now report that the activity of orexin neurons, a discrete cell population in the lateral hypothalamus that is involved in the circadian sleep/wake cycle and arousal, is modulated by IGF-I. Furthermore, mice with blunted IGF-I receptor activity in orexin neurons have lower levels of orexin in the hypothalamus, show altered electro-corticographic patterns with predominant slow wave activity, and reduced onset-sleep latency. Collectively, these results extend the role in the brain of this pleiotropic growth factor to shaping sleep architecture through the regulation of orexin neurons. We speculate that poor sleep quality associated to diverse conditions may be related to disturbed brain IGF-I input to orexin neurons. © 2020 Federation of American Societies for Experimental Biology